2018
DOI: 10.1109/tits.2017.2776354
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Model-Based Design and Implementation of Supervisors for Advanced Driver Assistance Systems

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…For the requirements, we identify textual formats that can straightforwardly be translated into models. This method produces models that show similarities to the models of a theme park vehicle (Forschelen et al 2012), a patient support table for an MRI scanner (Theunissen et al 2014), a FESTO production line (Reijnen et al 2018), and a driver assistance system (Korssen et al 2018). While these papers all present their models in detail, none of them discusses a method to obtain those models.…”
Section: Modeling Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the requirements, we identify textual formats that can straightforwardly be translated into models. This method produces models that show similarities to the models of a theme park vehicle (Forschelen et al 2012), a patient support table for an MRI scanner (Theunissen et al 2014), a FESTO production line (Reijnen et al 2018), and a driver assistance system (Korssen et al 2018). While these papers all present their models in detail, none of them discusses a method to obtain those models.…”
Section: Modeling Methodsmentioning
confidence: 99%
“…By far, most cases described in the literature focus on the domain of manufacturing systems; e.g., Leduc and Wonham (1995), Brandin (1996), Lauzon et al (1996), Kim et al (2001), de Queiroz and Cury (2002), Chandra et al (2003), Nourelfath and Niel (2004), Ljungkrantz et al (2007), Pétin et al (2007), Hasdemir et al (2008), Moor et al (2010), Silva et al (2011), van der Sanden et al (2015, and Pena et al (2016). Other application domains are theme park vehicles (Forschelen et al 2012), chemical process control (Rawlings et al 2014), patient support table for an MRI scanner (Theunissen et al 2014), smart homes dedicated to disabled people (Guillet et al 2014), mobile robots (Lopes et al 2016), computer science (Liao et al 2013;Auer et al 2014;Atampore et al 2016), and driver assistance systems (von Bochmann et al 2015;Korssen et al 2018). In Reijnen et al (2017), we reported on an application related to a lock control system in Tilburg.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Case ADAS. In this case study, an Advanced Driver Assistant Systems (ADAS) is modeled, see [13]. In such an application, a supervisor is synthesized to safely switch in a vehicle between the modes 'no cruise control (NCC)', 'cruise control (CC)', and 'adaptive cruise control (ACC)'.…”
Section: Case Studies Descriptionmentioning
confidence: 99%
“…The syntheses in this paper are performed using the EFA supervisor synthesis tool of CIF 1 . CIF has been used to synthesize supervisors for industrial sized systems [4]- [6], [22], [23]. Its EFA supervisor synthesis tool is based on the supervisor synthesis algorithm sketched in Section II-A, barring some minor differences that are irrelevant to our interpretation of the algorithm.…”
Section: B Cif Toolsetmentioning
confidence: 99%